RETRACTED: Empowerment of Increasing Economic Resilience Post Covid-19 Janjang Wulung Village Community Through Creative Economic Village Planning - Wardhana, Alvian; Ramayuda, Muhammad; Muhammad, Faza Farhan; Nariswari, Acyuta Putri; Cahya, Salsa Dwi; Wicaksono, Garin Ardi; Dianafi, Dani Rizky; Ivan, Muhammad (CSID Journal of Infrastructure Development, 2024)
This article has been retracted at the request of the authors. Reason: 1. Conflict of interest for using an open database under the assignment of “Studio Desa” on the odd semester 2020/2021 at Perencanaan Wilayah dan Kota, Universitas Brawijaya 2. The plaintiff's consideration comes from another researcher under the assignment of “Studio Desa” related to the reconstruction of Journal results and development 3. Avoid bigger conflicts, especially those related to all parties, including authors, Plaintiff parties, institutions, and all parties involved The Publisher